Identification and Structure Analysis of KCS Family Genes Suggest Their Reponding to Regulate Fiber Development in Long-Staple Cotton Under Salt-Alkaline Stress - Rui, Cun; Chen, Xiugui; Xu, Nan; Wang, Jing; Zhang, Hong; Li, Shengmei; Huang, Hui; Fan, Yapeng; Zhang, Yuexin; Lu, Xuke; Wang, Delong; Gao, Wenwei; et al. (Frontiers in Genetics, 2022)
Plant 3-ketoacyl-CoA synthase (KCS) gene family catalyzed a β ketoacyl-CoA synthase, which was the rate-limiting enzyme for the synthesis of very long chain fatty acids (VLCFAs). Gossypium barbadense was well-known not only for high-quality fiber, which was perceived as a cultivated species of Gossypium. In this study, a total of 131 KCS genes were identified in four cotton species, there were 38, 44, 26, 23 KCS genes in the G. barbadense, the G. hirsutum, the G. arboreum and G. raimondii, respectively. The gene structure and expression pattern were analyzed. GBKCS genes were divided into 6 subgroups, the chromosome distribution of members of the family were mapped. The prediction of cis-acting elements of the GBKCS gene promoters suggested that the GBKCS genes may be involved in hormone signaling defense and the stress response. Collinearity analysis on the KCS genes of the four cotton species were formulated. Tandem duplication played an indispensable role in the evolution of the KCS gene family. Specific expression analysis of 20 GBKCS genes indicated that GBKCS gene were widely expressed in the first 25 days of fiber development. Among them, GBKCS3, GBKCS8, GBKCS20, GBKCS34 were expressed at a high level in the initial long-term level of the G. barbadense fiber. This study established a foundation to further understanding of the evolution of KCS genes and analyze the function of GBKCS genes.